Thermal neutron scattering data for 7LiF and BeF2 - Wang Jia; Song Hongzhou; Hu Zehua; Ye Tao; Sun Weili (EPJ Web of Conferences, 2017)
Based on the coherent elastic, incoherent elastic, coherent inelastic and incoherent inelastic scattering processes, a code named SIRIUS is developed to produce thermal neutron scattering data for crystals in ENDF-6 format. The phonon band structures and projected phonon densities of states of 7LiF and BeF2 crystals were calculated by Hellman-Feynman Theorem combined with a lattice dynamics direct method. Finally the thermal neutron scattering data for 7LiF and BeF2 crystals are given.